2006
DOI: 10.1111/j.1744-9987.2006.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte and Monocyte Adsorption Apheresis (GCAP) for Refractory Skin Diseases Caused by Activated Neutrophils and Psoriatic Arthritis: Evidence that GCAP Removes Mac‐1‐Expressing Neutrophils

Abstract: In the present study, we have shown that granulocyte and monocyte adsorption apheresis (GCAP), an extracorporeal apheresis instrument whose column contains cellulose acetate (CA) beads, is useful for skin diseases attributable to activated granulocytes and psoriatic arthritis (PsA). We assessed the clinical effectiveness of GCAP and investigated the mechanisms underlying the adsorption of pathogenic granulocytes. The effect of GCAP was assessed in 14 patients with neutrophilic dermatoses and 16 with PsA. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 23 publications
2
76
1
Order By: Relevance
“…The appearance of similar granulocyte abnormalities in individuals with defects in adjacent steps of the cholesterol synthesis pathway could be coincidental. However, granulocyte/neutrophil-rich pathology is also characteristic of psoriasis and psoriatic arthritis, and our findings suggest a direct association between demethylation of MASs and innate immunity (38,39). It is also intriguing to speculate that the mild elevation of 4,4′-dimethylsterols seen in the patient's father could be relevant to his history of early-onset inflammatory joint disease.…”
Section: Figurementioning
confidence: 59%
“…The appearance of similar granulocyte abnormalities in individuals with defects in adjacent steps of the cholesterol synthesis pathway could be coincidental. However, granulocyte/neutrophil-rich pathology is also characteristic of psoriasis and psoriatic arthritis, and our findings suggest a direct association between demethylation of MASs and innate immunity (38,39). It is also intriguing to speculate that the mild elevation of 4,4′-dimethylsterols seen in the patient's father could be relevant to his history of early-onset inflammatory joint disease.…”
Section: Figurementioning
confidence: 59%
“…This approach is already used as a therapeutic strategy for other inflammatory diseases. Indeed, some extracorporeal apheresis systems (for example, cellulose acetate beads) have been developed to remove activated monocytes and granulocytes in order to treat specific refractory and inflammatory diseases associated with leukocytes such as ulcerative colitis, neutrophilic dermatosis and psoriatic arthritis [27-29]. More recently, Humes et al .…”
Section: Discussionmentioning
confidence: 99%
“…The CA beads in the column activate and adsorb complement component iC3b, a ligand for Mac‐1 that is a cell‐surface adhesive molecule expressed on activated granulocytes and monocytes. Based on these facts, we previously demonstrated that the column selectively traps activated granulocytes by binding Mac‐1 expressed on the granulocytes to iC3b on the beads . It was initially approved for the treatment of ulcerative colitis .…”
Section: Discussionmentioning
confidence: 95%
“…Based on this and previous experience and in vitro observations, we posit that GMA is a useful treatment modality for refractory skin diseases attributable to activated granulocytes. Our favorable experience in the present case suggests that GMA is safe and useful in pregnant and non‐pregnant patients.…”
Section: Discussionmentioning
confidence: 99%